A new species of Microvelia (Insecta: Hemiptera: Heteroptera: Gerromorpha) from coastal Espírito Santo State, with a key to the species of the genus recorded from southeastern Brazil JÉSSIKA ANA RÚDIO & FELIPE FERRAZ FIGUEIREDO MOREIRA (Brazil) - Rúdio, Jéssika Ana; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2011)
Microvelia nessimiani sp. nov. from coastal Espírito Santo State, Brazil, is described, illustrated, and compared with similar species. An identification key to the species of Microvelia so far recorded from southeastern Brazil is presented.